Food safety knowledge, attitude, and hygiene practices (KAP) and microbial quality of meat in slaughterhouses: a study in gopalganj, Bangladesh - Nur Mohammed Imran Hossain; Md Entaduzzaman Jony; Progati Bakshi; Juwel Rana; Zannatul Ferdoush; Md Golam Maula Shomrat; Md Mehedi Hasan Titu; Daniel Chakma; Lima Khatun; Muha Rakibul Islam (Journal of Agriculture and Food Research)
Poor hygiene and limited food safety awareness among meat handlers contribute significantly to foodborne diseases in Bangladesh. This study assessed the microbiological quality of raw meat in slaughterhouses across Gopalganj district and evaluated the knowledge, attitudes, and practices (KAP) of meat handlers. A cross-sectional survey of 60 meat handlers from 20 slaughterhouses was conducted between February and October 2024 using structured questionnaires, and 100 raw meat samples underwent microbiological analysis for Total Staphylococcus aureus Count (TSAC), Total Viable Count (TVC), and Total E. coli Count (TEC).Findings revealed that only 28.3 % of handlers had adequate food safety knowledge (mean score: 8.12 ± 3.03 out of 20). Positive attitudes were observed in 88.3 % (mean score: 46.19 ± 8.28 out of 75), but only 30 % exhibited good hygiene practices (mean score: 25.63 ± 8.9 out of 75). Education level was significantly associated with food safety practices (p = 0.021), while other demographic factors showed no significant associations with KAP. Significant positive correlations (p < 0.001) were found between knowledge, attitudes, and practices. Microbial analysis showed widespread contamination, with 93 % and 87 % of meat samples exceeding acceptable TEC and TSAC limits, respectively. Gopalganj Sadar recorded the highest TVC (7.76 log10 CFU/g), while Kashiani showed the highest TEC (4.56 log10 CFU/g) and TSAC (5.08 log10 CFU/g).These findings highlight the urgent need for slaughterhouse infrastructure improvements and targeted training programs to mitigate contamination risks and safeguard public health.